2000
DOI: 10.1002/1522-726x(200008)50:4<426::aid-ccd12>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of thrombocytopenia following coronary stent placement using abciximab plus clopidogrel or ticlopidine

Abstract: The incidence of thrombocytopenia with ticlopidine and clopidogrel when used in conjunction with abciximab has not been systematically addressed. We evaluated the rate of thrombocytopenia in patients undergoing intracoronary stent implantation receiving bolus plus infusion of abciximab and either ticlopidine or clopidogrel. We noted an incidence of 24% with the combination of 300-mg clopidogrel and abciximab. Other doses of ticlopidine (250 and 500 mg) and clopidogrel (75 mg) did not result in a statistically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…On the other hand, the majority of our patients in both treatment groups were also treated with abciximab and the frequency of bleeding complications or severe thrombocytopenia in the present study is compatible with that encountered in previous trials on abciximab therapy [23, 24]. Therefore, our findings are in contrast with those of a study in 25 patients according to which the combination of a loading dose of clopidogrel with abciximab during stenting further increased the risk for thrombocytopenia [25].…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, the majority of our patients in both treatment groups were also treated with abciximab and the frequency of bleeding complications or severe thrombocytopenia in the present study is compatible with that encountered in previous trials on abciximab therapy [23, 24]. Therefore, our findings are in contrast with those of a study in 25 patients according to which the combination of a loading dose of clopidogrel with abciximab during stenting further increased the risk for thrombocytopenia [25].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, Taniuchi et al [32] showed in 228 patients treated with clopidogrel (300 mg loading dose) in conjunct with GPIIb/IIIa receptor antagonists that the incidence of thrombocytopenia was not significantly higher for combination therapy as compared for the respective GPIIb/IIIa receptor blockers alone. In contrast a higher incidence of thrombocytopenia in patients receiving an oral loading dose of 300 mg clopidogrel in conjunction with abciximab was reported [19]. Moreover, it could be demonstrated that abciximab combined with unfractionated heparin leads to a significant increase in mild and severe thrombocytopenia, whereas this effect could not be shown for unfractionated heparin in conjunction with the small molecule GP IIb/IIIa receptor inhibitors [31].…”
Section: Discussionmentioning
confidence: 92%
“…Development of thrombocytopenia within 24 h is most likely caused by the administration of the glycoprotein IIb/IIIa-antagonists abciximab, eptifibatide and tirofiban, respectively [17, 19,22]. It has been discussed that binding of the antagonists to the glycoprotein receptor may lead to exposure of a ligand induced binding site which is then recognized by either preexisting or inducable antibodies [17,28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations